"A piece of paper is not the same as having someone to talk to": accessing post-diagnostic dementia care before and since COVID-19 and associated inequalities - Clarissa Giebel; Kerry Hanna; Hilary Tetlow; Kym Ward; Justine Shenton; Jacqueline Cannon; Sarah Butchard; Aravind Komuravelli; Anna Gaughan; Ruth Eley; Carol Rogers; Manoj Rajagopal; et al. (BMC, 2021)
Abstract Background Social support services such as day care centres are important in post-diagnostic dementia care to enable people living with dementia stay at home for longer. Little research has addressed potential inequalities in access, with no research on variations before and since COVID-19. The aim of this study was to explore inequalities in social support service usage before and since the pandemic. Methods Unpaid carers and people living with dementia were interviewed over the phone about their experiences of accessing social support services before and since the COVID-19 pandemic. Transcripts were analysed for key themes using inductive and deductive thematic analysis. Results Fifty participants (42 unpaid carers; eight people living with dementia) were interviewed, and five themes identified: (1) Service issues; (2) Access issues; (3) Relying on own initiative; (4) New inequalities due to COVID-19; and (5) Missing out on the benefits of support services. Participants reported transport, finances, and location as factors reducing their ability to access support service pre-COVID, with inequalities remaining and at times exacerbated since. Carers and people living with dementia also reported struggling with accessing basic necessities during COVID, including food and medicines. Conclusions Considering the benefits of accessing support services, resourced procedures and facilities are needed to maintain access to support services with more accessible remote support provision, enabling people from all backgrounds to access the care they need.